The refusal of the victim's family to testify in the trial - Huerta Molina, John Franck (2024)
The importance of the victim’s testimony in the Peruvian criminal process is so significant that it has been addressed by the Supreme Court of Justice of Peru. Plenary Agreement No. 2-2005/CJ-116 established that the victim’s testimony must pass through a filter—truthfulness indicators—to be considered valid evidence capable of undermining the presumption of innocence of the defendant. Plenary Agreement No. 5-2016/CJ-116 reiterates that in cases of violence against women and family members, the truthfulness indicators must be applied to the victim’s testimony. This has subsequently been legalized in the Regulations of Law No. 30364, Law to Prevent, Punish, and Eradicate Violence against Women and Family Members, Supreme Decree No. 009-2016-MIMP, dated July 27, 2016. On the other hand, the right of refusal of the defendant’s family witness is a legal provision with constitutional roots; however, in many cases, that family member called to testify in the oral trial is the victim themselves. Thus, it raises the question of whether it is permissible for such a witness-victim to abstain from testifying. The issues discussed contain a sense of procedural criminal problematic; however, there is a more delicate underlying issue, which is the purpose of criminal procedural law. The reflections developed were based on judicial pragmatism that aims to facilitate the pursuit of truth and, therefore, the approach to justice.